History and Eschaton — Eschatology and Existence - Мидић, Игнатије (Sabornost - The Theological Year-book, 2015)
This research aims to answer the following questions: What is the purpose of the world, and final event in its history? Is the final event of history (Eschaton) an addendum or a supplement to history like all others historical events? Namely, does it directly affect the existence or non‑existence of history itself? If the Paradise and the Hell were only some psychological states of the soul, or these words marked simply common life of human beings and angels in Eschaton, how could we explain the state of pain and suffering of sinners in the context of the Eternal Life? What is the role of Christ in salvation?